The Development of Daddy Hero Fitness Center using Web Based System - Chan Jia Yau; Firkhan Ali Bin Hamid Ali (Applied Information Technology And Computer Science, 2021)
For the legacy management system in Daddy Hero Fitness is use of notebook to record trainer and trainee. The problem is the data is on risk if notebook damage or missing. Next, the management for trainer to trainee need to use other software to make trainee workout program. Its is no effective when all the data need to type again and make similar program for each trainee. Addition, trainee unable to know how much workout they done and payment details for their payment. So, this system will record all data on online database with a web-based management system. Next, provide exercise and foods details for trainer to make diet and workout plan to customize program for trainee. For trainee, it will display the program with trainer name, health status data and payment details for them. To develop this system by using waterfall method since it is a small management system and collected clear user requirements before design the system. By using entity relationship diagram to design the database and data flow diagram for data flow of this system. For development and implementation, by using Hypertext Preprocessor, JavaScript, HyperText Markup Language and Cascading Style Sheets to make a web-based system. Lastly, perform system functionality testing and evaluation. Finally, discuss the achievement for objectives and future works for this system.